Analisis Kesalahan Penerjemahan Teks Bahasa Arab Siswa MA Al-Basyariyyah dalam Segi Frasa Nomina dan Adjektiva - Alviona Dwinanda Sari; Maman Abdurrahman; Rinaldi Supriadi (Taqdir, 2024)
Errors in translating foreign languages are very common, especially among students, whether they are in elementary school, middle school, or university. This study aims to analyze translation errors in students, focusing on noun phrases and adjective phrases. The method used in this research is qualitative, employing a case study design with the subjects being tenth-grade students of MA Al-Baysariyyah. The data were obtained from test results and documentation, and were then analyzed using error analysis techniques by identifying errors, classifying them, and subsequently correcting the identified errors. The results of this study show that students made translation errors in noun phrases and adjective phrases, which are further categorized. In noun phrases, errors are viewed from the perspective of idhafah requirements and i’rab. In adjective phrases, errors are viewed from the perspective of definiteness, i’rab, number, gender, and the type of adjectives